3-[(3,4-Dichlorophenyl)aminocarbonyl]propionic acid monohydrate - Gowda, B. Thimme (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(10)H(9)Cl(2)NO(3)·H(2)O, the conformations of the amide O atom and the carbonyl O atom of the acid segment are anti to the H atoms of adjacent –CH(2) groups. In the crystal, the molecules are linked into a three-dimensional network through N—H⋯O and O—H⋯O intermolecular hydrogen bonds.